Atypical manifestation of giant thyroid goiter: a case report presenting with Arm paresthesia - Chiu, Po-Yu; Lin, Che-Hsuan; Lu, Shih-Chun; Yueh, Hann-Ziong (Frontiers in Surgery, 2025)
A 61-year-old male presented with persistent numbness, weakness, and soreness in his left arm. Imaging and fine-needle aspiration cytology indicated a benign thyroid nodule, which was subsequently confirmed by postoperative pathology. The patient recovered uneventfully following surgery, with no evidence of recurrence during follow-up. While large thyroid nodules typically cause tracheal compression, dysphagia, or compromised vascular flow, this rare case involved a mass effect compressing the brachial plexus, resulting in neurological symptoms such as numbness, weakness, and soreness.